2013
DOI: 10.1080/15205436.2012.690926
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Characters’ Bad Behaviors Acceptable? The Effects of Character Motivation and Outcome on Perceptions, Character Liking, and Moral Disengagement

Abstract: Resumen. El diseño de concepto es el puente entre la narrativa y las etapas de la producción (modelos, estructuras, animación, efectos, texturas). Para lograr una efectiva transición, es necesario que, desde el diseño de concepto como intermediador entre la plástica y la mecánica, se construya la estética general del proyecto animado a partir del diseño de personajes u objetos y el acting para generar un vínculo empático con el público. La sistematización de la experiencia estará enfocada en el personaje prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 32 publications
1
56
0
4
Order By: Relevance
“…A recent study suggests that even though MACs have been part of the television landscape for a long time, over the last years there has been a significant increase in their presence in the television landscape (Daalmans, Hijmans, & Wester, 2013). Therefore, scholars have started to more systematically study characters with less clear-cut morality (e.g., Eden et al, 2011;Janicke & Raney, 2015;Krakowiak & Tsay-Vogel, 2013Shafer & Raney, 2012;Tamborini, Weber, Eden, Bowman, & Grizzard, 2010). Eden et al (2011) and Tamborini et al (2010) found that over the course of viewing narrative media, distinct hero, villain, and ambiguously moral characters emerge from ensemble casts, and can be identified by a) how well they uphold or violate moral norms, and b) how well they are rewarded or punished by the narrative, in line with ADT.…”
Section: Morality Predicts Enjoyment 351mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggests that even though MACs have been part of the television landscape for a long time, over the last years there has been a significant increase in their presence in the television landscape (Daalmans, Hijmans, & Wester, 2013). Therefore, scholars have started to more systematically study characters with less clear-cut morality (e.g., Eden et al, 2011;Janicke & Raney, 2015;Krakowiak & Tsay-Vogel, 2013Shafer & Raney, 2012;Tamborini, Weber, Eden, Bowman, & Grizzard, 2010). Eden et al (2011) and Tamborini et al (2010) found that over the course of viewing narrative media, distinct hero, villain, and ambiguously moral characters emerge from ensemble casts, and can be identified by a) how well they uphold or violate moral norms, and b) how well they are rewarded or punished by the narrative, in line with ADT.…”
Section: Morality Predicts Enjoyment 351mentioning
confidence: 99%
“…However, morality-based disposition formation processes may not apply as cleanly to narratives featuring morally ambiguous characters as they do to "pure" hero and villain characters. Recent research has addressed this gap by broadening the focus of character types to include morally ambiguous characters (MACs; Janicke & Raney, 2015;Krakowiak & Oliver, 2012;Krakowiak & Tsay-Vogel, 2013Shafer & Raney, 2012;van Ommen, Daalmans, & Weijers, 2014). These studies have primarily focused on the role of character moral ambiguity in predicting enjoyment.…”
mentioning
confidence: 99%
“…Usually, we are attracted to admirable or socially successful characters, and by those we share values, experiences or attitudes with (Bandura, 2001). We like characters whose actions and motivations we judge as appropriate (Hoffner and Cantor, 1991), although if we like a character we are able to provide a moral justification for their inappropriateness (Krakowiak and Tsay-Vogel, 2013). Researches show that liking makes the viewpoints, attitudes and actions of the characters better valued and taken into account (Hoffner and Tian, 2010; Moyer-Gusé et al, 2011).…”
Section: Involvement With the Charactermentioning
confidence: 99%
“…The affective disposition theory formula would suggest that viewers would disapprove of ambivalent characters' actions, and their enjoyment would correspondingly decrease. However, some research suggests that this does not seem to be the case (Krakowiak & Tsay-Vogel, 2013;Raney & Janicke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The primary interest of the academic community in MACs has mostly been part of an endeavor to better understand media enjoyment and not public morality (e.g., Eden, Grizzard, & Lewis, 2011;Krakowiak & Oliver, 2012;Krakowiak & Tsay-Vogel, 2013). Most of the studies, grounded in the affective disposition theory, find that moral considerations are central to character liking which then influences enjoyment (Raney, 2005;Zillmann & Bryant, 1975).…”
Section: Introductionmentioning
confidence: 99%